(untitled) (Journal of Comparative & International Higher Education, 2024)
Knowledge diplomacy has gained increasing traction as a goal for global higher education. Given its current construction, knowledge diplomacy has a focus on the role of higher education institutions in building formal global connectivity for common global good. This position paper argues for the inclusion of students’ education abroad programming as an important part of knowledge diplomacy for its individual and informal contribution to improving international relations and intercultural understanding. To achieve knowledge diplomacy through education abroad experiences, international educators need to guide students in small culture observations overseas as a mechanism to break down cultural stereotyping and to build cultural appreciation.